Hydromechanics for development of sprint canoes for the Olympic Games - Bugalski, T. J. (2009)
The current paper focuses on evolution of hull form of sprint canoes from the Olympic Games in Berlin (1936) to the Olympic Games in Beijing (2008) and the influence of hydrodynamics aspects on design of sprint canoes. The paper describes the process of the Olympic canoes design and optimization, carried out by the Ship Design and Research Centre (CTO, CTO S.A.) in Gdansk and the Plastex Composite PPH (Plastex) in Warsaw - the renowned manufacturer of sport boats. The existing canoes (used as a starting point) and the newly designed ones were analysed with the use of Computational Fluid Dynamics (CFD) methods, simplified potential methods and tested experimentally. The paper concludes the final results during Olympic Games competitions.